Pengaruh Latihan Renang Teratur dan Latihan Renang Tidak Teratur Terhadap Kadar Trigliserida Plasma pada Rattus norvegicus - Adi Wijayanto (Biotropic : The Journal of Tropical Biology, 2018)
Triglycerides are source of energy in the body, but triglyceride deposits that exceed the threshold will cause health problems, so triglycerides should be lowered to normal. The reduction of triglycerides can be done through physical activity, therefore this study aims to reveal the effect of regular swimming exercises and irregular exercises against triglyceride levels. This research is an experimental research using The Post Test Only Control Group Design design. Subjects of the study were male of Rattus Norvegicus Wistar, 39 subjects was divided into 3 groups with Matched Subject Design technique, which consisted of 2 groups of treatment that is regular and irregular group, and control group. The exercise program was given a swimming with a 3% weight of body weight and was tied 5 cm from the tip of the tail which was performed 3 times per week consistently for regular exercise and 0 to 5 times per week inconsistently for irregular exercise for 12 weeks, While the control group was not given training. In the last week before the blood was taken, the first three groups were given swimming treatment exercises. Based on the results of the anava test, there was a significant difference in the reduction of triglyceride levels among white mice who were given regular exercise with irregular exercise. These results suggest that regular exercise has a better impact on triglyceride reduction than irregular exercise, due to the higher adaptation process of regular exercise.